A memory of light [compact disc, unabridged] - Jordan, Robert, 1948-2007 (Jordan, Robert, 1948-2007. Wheel of time, 2013)
In the Field of Merrilor, the rulers of the nations join behind Rand al'Thor, or against him, to either aid or stop his plans to unseal the Dark One's prison--which could either be a sign of madness or the last hope of mankind. The Trollocks have seized Caemlyn, Perrin Aybara battles Slayer, and the fate of all humanity will be decided in Shayoul Ghul. The Wheel is turning and the Age is coming to an end. The last battle will determine the fate of the world in the final book of The Wheel of Time.